2004
DOI: 10.4049/jimmunol.172.10.5843
|View full text |Cite
|
Sign up to set email alerts
|

Shift from Systemic to Site-Specific Memory by Tumor-Targeted IL-2

Abstract: IL-2 has been approved for treatment of patients with cancer. Moreover, it has been used as a component of vaccines against cancer. In this regard, we have recently demonstrated that dendritic cell-based peptide vaccination in mice required IL-2 to mount an effective immune response against established melanoma metastases. In this study, we confirm this observation by use of tumor-targeted IL-2. However, the development of a protective systemic memory was substantially impaired by this measure, i.e., mice, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…This measure actually boosted the therapeutic effect of a TRP‐2 vaccine, resulting in the partial or complete regression of established tumors. However, it also interfered severely with the development of a protective, systemic memory (54). Indeed, high local concentrations of IL‐2 at the dermal/s.c.…”
Section: Syngeneic Transplantation Modelssupporting
confidence: 90%
“…This measure actually boosted the therapeutic effect of a TRP‐2 vaccine, resulting in the partial or complete regression of established tumors. However, it also interfered severely with the development of a protective, systemic memory (54). Indeed, high local concentrations of IL‐2 at the dermal/s.c.…”
Section: Syngeneic Transplantation Modelssupporting
confidence: 90%
“…CD8 ? T cells did not express increased levels of CD44 (compared with PBS controls), suggesting that IL-2 did not increase the induce effector memory T cells, which were site-specific, rather than central memory T cells [37]. Furthermore, others have shown that local IL-2 can induce a systemic response leading to the destruction of distant metastases [32,33,38].…”
Section: Discussionmentioning
confidence: 95%
“…B78-D14 melanoma is derived from B16F0, a cell line with C57BL/6 background, by transfection of genes coding for β-1,4-N-acetylgalactosaminyltransferase and α-sialyltransferase, inducing the expression of the disialogangliosides GD2 and GD3 (16,17). B16-EpCAM is a B16 variant expressing the EpCAM antigen (14).…”
Section: Cell Lines Preparation Of T Cells and Generation Of Dcsmentioning
confidence: 99%